Flow characteristics over coral reef - Ong, Kang Fu. (2009)
Understanding waves and the effects of its impact on coastal zones is essential to the design of coastal projects and the protection of the shoreline. In order to lessen the impact of the waves, and in turn minimizing the eroding nature of its force, coral reefs can be studied as they act as natural barriers in the shallow waters and help to protect the coastline from the waves. In general, there are three types of coral reef; fringing, barrier and atoll.